Thermal Reactions of Fullerenes with Cyclic Organosilicon and Organogermanium Compounds: Silylation and Germylation of C60 and C70. Issue 6 (25th September 2014) - Kako, Masahiro; Inaba, Daiki; Minami, Kazuya; Iida, Ryosuke; Nakahodo, Tsukasa; Akasaka, Takeshi
ABSTRACT Thermal reactions of empty fullerenes with disilirane (1) and digermirane (2) afforded the corresponding bis‐silylated and bis‐germylated derivatives. When a bicyclic fused silirane (3a) was heated in the presence of C70, two silylene adducts were obtained through thermal extrusion of silylenes. These results provide a complementary method to the photochemical addition of reactive silicon and germanium compounds, which have been long employed for derivatization of fullerenes. Electrochemical analyses revealed the redox properties of the silylated and germylated C70, indicating the electronic perturbation caused by silyl and germyl groups introduced on the fullerene cages. Theoretical calculations were also conducted for understanding of the electronic property of the fullerene derivatives.